2016
DOI: 10.1186/s12917-016-0813-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of Mycobacterium bovis causing pulmonary tuberculosis and epistaxis in a Thoroughbred horse

Abstract: Background: Tuberculosis caused by Mycobacterium bovis (M. bovis) is very uncommon in horses worldwide. Case presentation: In the current study, an eight-year-old male Thoroughbred in good body condition was admitted to the Equine Clinic at the Onderstepoort Veterinary Academic Hospital in 2005 due to bilateral epistaxis accompanied by coughing. Routine examinations were conducted to determine the cause of the condition. Endoscopic examination revealed the major source of the epistaxis as the trachea, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The four CWD management strategies used in North American free-ranging wild deer include 1) general, non-selective population harvest (spatially targeted); 2) selective or targeted removal of clinical suspects (infected deer); 3) seasonal harvest (eg, summer) and 4) vaccination 144. Predictive models that evaluated these management strategies found that increased general hunting pressure with or without targeted sex group, the role of large predators, and seasonal hunting had some positive effect on CWD under specific conditions 145147.…”
Section: Management Of Cwdmentioning
confidence: 99%
“…The four CWD management strategies used in North American free-ranging wild deer include 1) general, non-selective population harvest (spatially targeted); 2) selective or targeted removal of clinical suspects (infected deer); 3) seasonal harvest (eg, summer) and 4) vaccination 144. Predictive models that evaluated these management strategies found that increased general hunting pressure with or without targeted sex group, the role of large predators, and seasonal hunting had some positive effect on CWD under specific conditions 145147.…”
Section: Management Of Cwdmentioning
confidence: 99%
“…Pulmonary infections may cause coughing, pyrexia and epistaxis if there is a single tuberculous granuloma (Hlokwe et al . ), whereas secondary miliary pulmonary infiltration results in chronic weight loss, sternal oedema, dyspnoea, nasal discharge and exercise intolerance (Lyashchenko et al . ).…”
Section: Clinical Signsmentioning
confidence: 99%
“…; Hlokwe et al . ) and may present a greater zoonotic risk to personnel in close contact than the intestinal form.…”
mentioning
confidence: 99%
“…due to infection with M. bovis (Sarradell et al, 2015;Hlokwe et al, 2016), infections by M. avium are considered the most common cause of equine mycobacteriosis (Pavlik et al, 2008;Sano et al, 2014). Within the MAC complex, infections with M. avium subsp.…”
mentioning
confidence: 99%
“…Horses are relatively resistant to infection with mycobacteria (Pavlik et al, 2004;Sarradell et al, 2015). Mycobacterial infections in horses are caused by members of the MTC, particularly M. bovis (Sarradell et al, 2015;Hlokwe et al, 2016), or by members of the MAC, particularly M. avium subsp. avium (Pavlik et al, 2008;Ryhner et al, 2009).…”
mentioning
confidence: 99%